Ex-ante evaluation of India's trade alliance with Indo-Pacific region: A general equilibrium analysis - Archana Srivastava; Somesh K. Mathur; Prabir De (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2022)
This study attempts to analyse the economy wide impact of Indo-Pacific alliance between India and rest of the 45 participating countries. We introduce four simulation scenarios in the general equilibrium model. First scenario is the one in which India bilaterally liberalizes trade in terms of tariffs liberalization alone and then removal of tariffs and reduction of non-tariff barriers together with all the countries of Indo-Pacific region. Second scenario is when India bilaterally liberalizes trade with all the Asian countries of the Indo-Pacific region. Third scenario is when India bilaterally liberalizes trade with all the countries of the Indo-Pacific region but excludes China from the region because of the current geo-political constructs. Fourth scenario is the one when free trade is considered among all the countries in the Indo-Pacific region. The paper uses the GTAP (Global Trade Analysis Project) model simulations for the analysis and the results reveal that for India the welfare gains in terms of equivalent variation and real GDP are maximum in the third simulation scenario. The article suggests a roadmap for maximum welfare gains for India keeping strategic and economic engagements with other member countries and sub-regions.
Keywords: F15; 330; GTAP 10; Welfare Effects; Tariff; Non-Tariff Barriers; VGDP; Sectoral Impacts; Equivalent Variation; Indo-Pacific Alliance